Effect of Heracleum sosnowskyi extract aqueous solution on the Allium cepa root meristem - Smirnova, M. V.; Kotelnikov, V. A. (Regulatory Mechanisms in Biosystems, 2021)
Heracleum sosnowskyi (Apiaceae) contains a lot of useful chemical ingredients that can be used in industry, medicine and other fields as plant component extracts and as chemical compounds that have been extracted in different ways, which requires the last to be tested for chemical safety, including a genotoxic test in vivo. In the present paper, the 96-hour effect of the H. sosnowskyi extract aqueous solution at concentrations of 0.01, 0.05, 0.10, and 0.50 mL/L on the genetic apparatus and mitotic activity of the cells of the Allium cepa (Alliaceae) root meristem is discussed. Distilled water was applied as a negative control, and hydrogen peroxide 1% as a positive one. The extract was prepared from the plant’s fresh leaves by soaking them in acetone. It was then distilled at 57 ºС and diluted with distilled water to obtain the experimental concentrations. As extract content in the aqueous solution increased, a statistically significant decrease in mitotic activity, an increase in aberrant cell percentage and a concentration-dependent inhibition of root growth were observed. In the 0.5 mL/L solution, if compared against the other experimental concentrations, an increase in the metaphase, anaphase and telophase indices along with a decrease in the prophase index were observed. The most common aberrations for all the concentrations were lagging and sticking chromosomes, anaphase bridges, ring chromosomes and nuclear buds. The same solution and the positive control produced membrane damage; giant and ghost cells. The results of the experiment performed have demonstrated the extract’s aneugenic effect that causes spindle disturbance, mitodepression and inhibits the cells of the Allium cepa root meristem, prevails over its clastogenic effect.